Cloud computing in Malaysia Universities - Razak, Siti Fatimah Abdul (2009)
Students in the 21(st) century can no longer be confined to traditional teaching-learning methods, i.e. lecturing and tutoring which is commonly used in Universities. Universities from around the global have recognized needs to adapt new teaching-learning approach to meet students' diverse need. This paper will briefly discuss cloud computing and the possible benefits or offerings cloud computing have for Universities especially in Malaysia. We will also look into a few challenges that need to be recognized by Universities in adapting cloud computing into the teaching-learning environment.